Radiofrequencies in low back pain PDTA - Damiana Maurogiovanni; Daniele Bertollo; Gianpaolo Fortini (Publiediting, 2023)
The authors present the proposal of a specific therapeutic diagnostic pathway; the quality of care and the journey of the citizen/patient affected by low back pain. They also present the results of a retrospective study aimed at verifying the impact that radiofrequency procedures have within this DPT.